Implementasi Kurikulum Kulliyatul Mu’allimin Wal Mu’allimat Al-Islamiyah (KMI) Di Pondok Pesantren Al-Ikhlas Taliwang - Jajang Haris Bin Andi; Husnul Khotimah (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
Curriculum is the important one in any particular educations formal or informal. Then how to implement it in reaching the purpose of education, because the implementation of curriculum as process system of putting an agreed plan, decision, proposal, idea or policy in order to give the good effect on the change, skill, or value, manner and attitude effectively and efficiently. And it’s also as the real action of planning to make the concept, idea, program, or structure curriculum on learning new activities in order to change the group of students are expected. Therefor the implementation of KMI curriculum means as process systems of action on activities, idea, program by doing hard based to the true norm to reach the purpose of education.